A Composite Study of Coeliac Trunk in 30 Adult Human Cadavers - its Clinical Implications. (Global Journal of Medical Research, 2011)
Variations of origin and course of arteries of different organs are not only of anatomical and embryological interest but also of practical and clinical importance when these variations can be the agents of pathological conditions, or in surgery when knowledge of them can result in more accurate treatment. With the development of techniques of arteriography, the knowledge of arteries and of their variations has acquired a special importance for correct interpretation of the different, and sometimes very complicated roentgenographic pictures. Anatomical variations involving the visceral arteries are common. However though variations in coeliac trunk are usually asymptomatic, they may become important in patients undergoing diagnostic angiography for gastrointestinal bleeding or prior to an operative procedure. Recognition of variations enables clinicians to distinguish features which merit further investigations or treatment from those which do not. Clinical implications of variations in this artery have been stressed upon.
Keywords: Coeliac trunk; Gastric artery; Hepatic artery; Splenic artery